Cost–Benefit Analysis of Solar Energy Utilization in Households: An Economic ‎Evaluation - Devi, Dr. D. Sasikala (International Journal of Accounting and Economics Studies, 2025)
The advent and rise of electricity as a necessity, and the environmental problems or concerns that accompany the use of traditional fossil-based sources of power, have given the argument in favor of implementing sustainable energy systems in households strong support. ‎Solar energy is now an option with economic and environmental ‎benefits that would be beneficial to the household. Problems with initial establishment cost, ‎opportunity costs, and uncertainty in the financial payoff continue to influence household ‎adoption decisions. The paper shall seek to perform a cost-benefit analysis on the application ‎of solar energy in a household, specifically with respect to the opportunity cost of using solar ‎energy and comparing the economic implications of using solar energy and the traditional ‎consumption of electricity.‎This study followed the quantitative research design, whereby a survey of 100 households was ‎carried out with secondary data collection tools such as government and policy reports. The ‎trend in baseline consumption and expenditure was selected through descriptive statistics, ‎and inferential analysis was selected in order to provide more information about financial ‎results. Paired sample t-test compared the expenditure on household electricity in pre- and post-adoption of solar energy, and savings in the new phase were found to be significant. The ‎independent variables of net financial benefits were calculated using multiple regression ‎, where the consumer units of net financial benefits, solar-generated units, imported units, and ‎with- and without-solar costs were important predictors. The opportunity cost estimation ‎indicated that the comparative advantage of investing in solar energy relative to the constant ‎conventional expenditure had a strong effect of 643.22 R on the household savings on a ‎monthly basis, and substantial savings in the dependence on a grid-based power source.‎The findings show that though adoption of solar energy is costly in the short run, its economic ‎benefit is higher in the long run, and most importantly, the consumption cost of solar energy is ‎considerably low by its comparison to the use of fossil fuels. Results of studies declare that, in ‎addition to the viability of the economy, the deployment of solar is also strategically feasible ‎in localities where households have an opportunity to save cash and, in addition, ensure that the ‎shifts to sustainability in energy are accomplished. The occupants of the houses will be ‎influenced to make a decision on green energy using the findings, and also sway the ‎debate to implement clean energy in the developing economies‎.
Keywords: Solar Energy Utilization; Cost–Benefit Analysis; Household Electricity Consumption; ‎Opportunity Cost; Renewable Energy Adoption; Economic Feasibil-ity; Sustainable Energy ‎Transition